2016
DOI: 10.1016/j.gca.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

In situ observations of liquid–liquid phase separation in aqueous ZnSO4 solutions at temperatures up to 400 °C: Implications for Zn2+–SO42− association and evolution of submarine hydrothermal fluids

Abstract: spectroscopic observations of the liquid-liquid immiscibility in aqueous uranyl sulfate solutions at temperatures up to 420 circ C, The Journal of Supercritical Fluids http://dx.doi.org/10. 1016/j.supflu.2016.03.005 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 141 publications
1
27
0
Order By: Relevance
“…As the concentration increases, the presence of a Raman band (260 cm −1 ) has been assigned to [Zn 2+ ⋅OSO 3 2− ] ligand mode in the inner‐sphere complexes ion‐pair. As studied of vibration of Zn‐O mode in MOF pores, the amplified peak of [Zn 2+ ⋅OSO 3 2− ] ligand mode substantiated a more constrict complex ion, which seems impossible to be realized in solubility‐limited ZnSO 4 solutions . We then further analyzed the variation trend of O−H stretch vibration as concentration increases and found that band shift to high frequency (HOH−OH 2 stretch, 3264–3304 cm −1 , Figure c) .…”
Section: Figurementioning
confidence: 93%
See 1 more Smart Citation
“…As the concentration increases, the presence of a Raman band (260 cm −1 ) has been assigned to [Zn 2+ ⋅OSO 3 2− ] ligand mode in the inner‐sphere complexes ion‐pair. As studied of vibration of Zn‐O mode in MOF pores, the amplified peak of [Zn 2+ ⋅OSO 3 2− ] ligand mode substantiated a more constrict complex ion, which seems impossible to be realized in solubility‐limited ZnSO 4 solutions . We then further analyzed the variation trend of O−H stretch vibration as concentration increases and found that band shift to high frequency (HOH−OH 2 stretch, 3264–3304 cm −1 , Figure c) .…”
Section: Figurementioning
confidence: 93%
“…In MOF pores, the ν‐SO 4 2− band remarkably shifts to higher frequency (ca. 992 cm −1 ), which indicates an unique solvation structure where Zn 2+ is highly constrained with anions to form a more close [Zn 2+ SO 4 2− ] ion association . Figure b exhibits a polarized band (Zn‐OH 2 vibration, ca.…”
Section: Figurementioning
confidence: 98%
“…Similarly, the formation of immiscible, dense liquid phases at high temperatures has been identified in situ using the ratios of sulfate and OH Raman spectral band areas and the formation of new bands that correspond to polymeric mixtures [44,45]. These dense fluid phases play an important role in mineral nucleation [7] when it occurs via a non-classical route [46] as well as element transport [45].…”
Section: Examining the Properties Of Ions In Solution Using Raman Spementioning
confidence: 99%
“…As studied of vibration of Zn-O mode in MOF pores, the amplified peak of [Zn 2+ ·OSO 3 2À ] ligand mode substantiated a more constrict complex ion, which seems impossible to be realized in solubility-limited ZnSO 4 solutions. [19] We then further analyzed the variation trend of OÀH stretch vibration as concentration increases and found that band shift to high frequency (HOHÀOH 2 stretch, 3264-3304 cm À1 , Figure 2 c). [20] This intensity of O À H stretch vibration is sharply suppressed, further confirming a small minority of water in MOF pores.…”
mentioning
confidence: 99%
“…992 cm À1 ), which indicates an unique solvation structure where Zn 2+ is highly constrained with anions to form a more close [Zn 2+ SO 4 2À ] ion association. [19] Figure 2 b exhibits a polarized band (Zn-OH 2 vibration, ca. 390 cm À1 ), which can be appeared both in inner-sphere and outer-sphere ion-pairs.…”
mentioning
confidence: 99%